Analysis of Aggregate Interference and Primary System Performance in Finite Area Cognitive Radio Networks - Vijayandran, L.; Dharmawansa, P.; Ekman, T.; Tellambura, C. (IEEE transactions on communications, 2012)
This paper considers the analytical performance of primary users (PUs) subject to interference due to secondary users (SU) in an underlay cognitive radio system over Rayleigh fading. In particular, we focus on a more general spatial configuration where the interfered PU, not only located at the center of the cell, is having a protective region which is free of SUs and the SUs are distributed over a finite area in contrast to the commonly used infinite area assumption. We first characterize the statistical properties of the aggregate interference at the PU due to SUs, by deriving new exact closed form expressions for the moment generating function, cumulants, first, second and third moments and first order expansions of the cumulative distribution functions corresponding to propagation scenarios with path loss factors, two and four. We then investigate the PU performance by presenting new analytical expressions for the outage probability, amount of fading as well as the diversity order and coding gain. Our results indicate that the PU can achieve the full diversity gain given a non-zero protective region around the PU.